Gender and Property Rights in Sub-Saharan Africa : A Review of Constraints and Effective Interventions - O'Sullivan, Michael (World Bank, Washington, DC, 2017)
Strengthening women's ownership, control, and use of land, livestock, and savings assets matters for poverty and shared prosperity, as unequal property rights can lead to intrahousehold inequality in wealth; allocative inefficiencies, which are costly in lost economic output and productivity growth; and women's control over household resources and spending decisions, with welfare implications for this generation and the next. Yet, there is ample evidence to show that the distribution and control of these key assets are skewed toward men across Sub-Saharan Africa. This paper examines the underlying constraints that potentially give rise to these inequalities, assesses the impact evaluation evidence on how to narrow existing gaps and boost welfare, and outlines a set of priority research and policy questions. On land, the review uncovers promising evidence on joint land titling and notes the need for work from urban settings and complementary interventions that address multiple market failures. On savings, those products with an element of illiquidity and a soft commitment show promise for women in experimental settings. On livestock, the review points to a striking dearth of evidence on the causal impact of livestock transfer programs -- aside from bundled ultra-poor programs and nutrition interventions.